Teacher Professional Identity and Curriculum Reform - Espinoza-Salfate, L (Springer Science and Business Media B.V., 2023)
The importance of teacher training, agency and identity in curriculum reform was strongly represented across theme E papers and discussions at the at the ICMI Study 24 conference. In this chapter, the authors address the professional dynamics stemming from the relationship between the stakeholders leading the development or refinement of the official curriculum and stakeholders responsible for translating the official curriculum into the classroom. In these translation and refinement processes, teachers can have different roles, according to their professional identity, and Wenger’s notion of trajectories can be used to understand teachers’ pathways through curriculum reforms. Specifically, teachers can act as co-constructors of the curriculum or as receivers of the curriculum. Possibly, they can transform their professional identities and cause shifts in what the authors call ‘reform ownership’ along a path from outside to inside the school. These dynamics contribute to the degree of agency and intellectual freedom afforded to, and felt by, the teachers responsible for translating curriculum documents into action in classrooms, which in turn has an impact on how effectively an official curriculum is implemented at a local level. © 2023, The Author(s).